Dopamine Drives Feedforward Inhibition to Orexin Feeding System, Mediating Weight Loss Induced by Morphine Addiction - Huiming Li; Sa Wang; Dan Wang; Jiannan Li; Ge Song; Yongxin Guo; Lu Yin; Tingting Tong; Haopeng Zhang; Hailong Dong (Advanced Science)
Abstract Feeding behavior changes induced by opioid addiction significantly contribute to the worsening opioid crisis. Activation of the reward system has shown to provoke binge eating disorder in individuals with opioid use disorder, whereas prolonged opioid exposure leads to weight loss. Understanding the mechanisms underlying these phenomena is essential for addressing this pressing societal issue. This study demonstrates that weight loss resulting from feeding behavior changes during morphine addiction requires the activation of the ventral tegmental area dopamine (DA) system, which suppresses the orexin feeding center. Specifically, DA exerts an inhibitory effect on orexin neurons in the lateral hypothalamus area (LHA) through a feedforward inhibition mediated by GABA neurons in the LHA, involving D1 receptors (D1R) and T‐type Ca2+ channels. Moreover, the morphine addiction‐induced reduction in body weight and food intake can be reversed by the D1R antagonist SCH23390 and chemogenetic silencing of GABA neurons in the LHA. These findings delineate a neuromodulatory mechanism underlying morphine addiction‐associated feeding behavior changes and weight loss.